Reformasi Pelayanan Publik di Dinas Investasi dan Pelayanan Terpadu Satu Pintu Kota Gorontalo - Djaafar, Lucyane (Universitas Gorontalo, 2018)
This study aims is to analyze; 1) Public service reform at the Department of Investment and One Gate Integrated Services Gorontalo City; 2) Determinant factors affecting public service reform at the Department of Investment and One Gate Integrated Services Gorontalo City. The research method used qualitative research, data collecting technique by observation, interview and documentation. The results showed that; 1). Public service reform at the Department of Investment and One Gate Integrated Services Gorontalo City seen from structure, procedure, process not yet run well but from behavioral element already showed existence of change of attitude of good apparatus in giving services; 2). The determinant factors affecting public service reform at the Capital Market and Department of Investment and One Gate Integrated Services Gorontalo City need to pay attention to the supporting factors of public service reform related to; 1) the awareness of the police officers in service; 2) rule enforcement; 3) organization; 4) income of employee; 5) human skill and resources; 6) facilities.